Desenvolvimento de Urochloa brizantha cv. Xaraés e atributos químicos do solo em função de diferentes doses e fontes de fósforo - Reis, Caroline Lucas dos (2020)
In view of the low levels of phosphorus in Brazilian soils and the need for this nutrient for the good development of pastures, the present work aimed to evaluate the chemical attributes of the soil and the development of Urochloa brizantha cv. Xaraés as a function of fertilization with different doses and sources of phosphorus. The experimental design was completely randomized, with a factorial arrangement 2x4 + 1, with nine treatments, which consisted of doses of P2O5 (0, 50, 100,150 and 200 kg ha-1), and two sources of phosphorus, the Triple Superphosphate and the Gafsa Reactive Natural Phosphate. The experiment was conducted in pots, in an open environment in the municipality of Rancharia-SP, with a completely randomized design. The following parameters were evaluated: chemical attributes of the soil (pH, phosphorus, calcium and base saturation), plant height, number of tillers, number of leaves, dry mass of aerial part and roots, leaf weight ratio, leaf analysis to determine nutrient content, chemical analysis to determine the content of crude protein, neutral detergent fiber (NDF), acid detergent fiber (FDA) and lignin, total soluble sugar content, with four evaluative cuts. The data obtained were submitted to analysis of variance (p <0.05) by the Tukey test, and the means compared to the control by the Dunnett test. Linear and polynomial regression analysis was performed to study the doses of the two fertilizers. The development of Urochloa brizantha cv. Xaraés was limited by the absence of phosphate fertilizer. The Triple Superphosphate source showed superior results in the first cuts for height, number of tillers, number of leaves and dry mass; however, in the fourth cut, the results of these variables for the two sources of phosphorus were similar. Gafsa's Reactive Natural Phosphate showed better results for soil chemical attributes, as well as for leaf phosphorus content. In the bromatological analysis, the sources of phosphorus showed similar results. Considering the responses obtained for both sources of phosphorus in relation to the doses of P2O5 used, the best results were observed in the dose range between 150 and 200 kg ha-1 of P2O5.